Negros, brancos e o grupo dos ricos: o outro lado da desigualdade racial brasileira - Emerson Ferreira Rocha (Ciências Sociais Unisinos)
This article discusses the determinants of racial inequality in the composition of the top incomes in Brazil. The results show that the factors explaining racial inequality behave unevenly across different levels of the income distribution, with the effect of discrimination reaching its maximum at the higher quantiles. This contradicts the thesis of “whitening” – embranquecimento – insofar as this thesis claims that blacks of a higher socioeconomic status may not suffer discrimination in Brazil or, at least, that they may be discriminated at a lesser extent. The data is from the 2010 Brazilian national Census. The methods are linear and non-linear regressions.